Effect of cultivation feed diet using local food processing by-products on the growth and flavor factor in the Malabar grouper Epinephelus malabaricus - Makoto Takahashi; Shingo Udagawa; Chihiro Yamauchi; Yoshimi Imura; Taekyoung Seong; Akihiro Takemura (Frontiers in Aquaculture)
IntroductionThis study investigated the use of locally sourced food processing by-products to formulate sustainable aquaculture feed in alignment with circular economy principles.MethodsAn experimental diet (Food Waste Diet; FW-D) was formulated using 50% fishmeal from tuna viscera and 20% brewer’s spent yeast (BSY) sourced in Okinawa, Japan. The Malabar grouper (Epinephelus malabaricus) were reared in a recirculating aquaculture system for 8 weeks and compared against a commercial diet (CO-D). Growth performance, liver somatic index, insulin-like growth factor 1 (IGF-1) gene expression, and muscle taste-related components were analyzed.ResultsFW-D-fed fish showed slightly lower growth performance, possibly due to decreased protein content. However, liver histology revealed no signs of metabolic stress, and IGF-1 gene expression levels were higher in the FW-D group, indicating active growth signaling. FW-D-fed fish also exhibited significantly increased muscle levels of unsaturated fatty acids, particularly docosahexaenoic acid (DHA), a nutrient beneficial for human health. Sensory analysis indicated comparable overall taste quality between the two groups. FW-D fillets had greater chewiness and reduced fishy odor, whereas CO-D fillets were richer in fatty taste.DiscussionThese findings suggest that FW-D, composed of locally available by-products, can offer a nutritionally advantageous and economically viable alternative to conventional feeds. Despite a slight reduction in growth, the enhanced DHA content and acceptable sensory attributes of FW-D-fed fish support its application in sustainable aquaculture systems. This approach contributes to resource recycling and value creation within a local circular economy.